PENGUATAN JIWA KEWIRAUSAHAAN DAN LITERASI AKUNTANSI UMKM PADA GURU DAN PEGAWAI SMP NEGERI 7 MALUKU TENGAH - Senda Yunita Leatemia; Emi Boki; Sari Tamayani Tjio; Zahra; Yana Mustika (Jurnal Pengabdian Masyarakat Sabangka, 2026)
In its development, the cultivation of entrepreneurial values is not only among entrepreneurs and the business world, but has also penetrated into the world of education. Entrepreneurship in education aims to make humans holistically, as human beings who have character, understanding, and skills as entrepreneurs. The problem related to the service carried out is whether teachers and school employees have an entrepreneurial spirit and understand the financial recording of the business being carried out. The purpose of this service is to obtain an overview of how to foster the spirit of entrepreneurship for teachers and school employees. The method of achieving this service goal is in the following stages (1) preliminary study (literature and field observation); (2) problem identification; (3) problem formulation; (4) determination of service goals; (5) socialization; (6) interviews; (7) analysis of service results; and (8) conclusions and suggestions.